Finite satisfiability verification in UML class diagrams: a comparative study - Bastos, P. (2016)
Unified Modeling Language class diagrams are widely used for modeling, playing a key role in the analysis and design of information systems, especially in development contexts that use modeling oriented methodologies. Therefore, it is relevant to ensure the creation and maintenance of correct class diagrams. With the use of class diagrams it is possible to specify classes, relations and restrictions, however, such diagrams are subject to modeling errors made by their authors and may degenerate into incorrect diagrams. A common cause of incorrect diagrams refers to the definition of contradictory and inconsistent constraints, leading to finite satisfiability problems. Several approaches to the verification of finite satisfiability are currently available, supported by different tools. Through this work, we proceed with the identification and comparison of the existing approaches for the verification of finite satisfiability in class diagrams, determining the effectiveness and efficiency of the proposed tools.